OPTIMIZATION OF MAIN FACTORS AFFECTING CONSTRUCTION WASTE BY THE SUPPLY CHAIN MANAGEMENT - Thanh Nguyen, Phong; Dang Vo, Khoa; Thanh Phan, Phuong; Le Hoang Thuy To Nguyen, Quyen; Bich Huynh, Vy Dang (International Journal of Supply Chain Management, 2019)
A survey report of the Vietnam Urban Environment and Industrial Zone Association reveals that every day in 2009, about 1,000 tons of construction waste were generated in Hanoi and 2,000 tons Ho Chi Minh City in Vietnam. It is forecasted that the coming years would see a vigorously growing amount of construction waste as a result of the plan to dismantle and renovate old apartment buildings in major cities. So, in this research we developed a supply chain management strategy for the waste controlling in the construction industry. While the bulky volume of construction wastes poses a great environmental threat to urban areas, response to it remains meager. Hence, this paper presents four primary factors affecting the management of construction wastes in Vietnam using fuzzy logic.